1995
DOI: 10.1007/bf00118102
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of carotenoids from various sources by rainbow trout: muscle colour, carotenoid digestibility and retention

Abstract: Rainbow trout (Oncorhynchus mykiss) with a mean (SD) weight of 120 (2)g were fed diets supplemented with astaxanthin extracted from the yeast Phaffia rhodozyma (OYl = 50 mg carotenoids kg& feed, OY2 = 100 mg carotenoids kg-' feed), astaxanthin (AX = 100 mg astaxanthin kg-' feed) and canthaxanthin (CX = 100 mg canthaxanthin kg' feed) for 4 weeks. Muscle analyses at the end of the experiment indicated a significantly higher carotenoid concentration in the AX group, while CX and OYl groups were similar in spite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
14
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 30 publications
5
14
0
Order By: Relevance
“…All the Phaffia diets provided concentrations of astaxanthin in the flesh that were statistically similar to that provided by the synthetic astaxanthin, Carophyll Pink. By contrast, Carophyll Pink fed to rainbow trout gave higher astaxanthin concentrations in the flesh than did extracted astaxanthin from Phaffia added to the test diet (Choubert et al 1995). Phaffia contains only the (3 R ,3′ R ) isomer (Andrewes and Starr 1976), whereas synthetic astaxanthin contains a mixture of (3 R ,3′ R ), meso‐(3 R ,3′ S ), and (3 S ,3′ S ) in a 1:2:1 ratio ().…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All the Phaffia diets provided concentrations of astaxanthin in the flesh that were statistically similar to that provided by the synthetic astaxanthin, Carophyll Pink. By contrast, Carophyll Pink fed to rainbow trout gave higher astaxanthin concentrations in the flesh than did extracted astaxanthin from Phaffia added to the test diet (Choubert et al 1995). Phaffia contains only the (3 R ,3′ R ) isomer (Andrewes and Starr 1976), whereas synthetic astaxanthin contains a mixture of (3 R ,3′ R ), meso‐(3 R ,3′ S ), and (3 S ,3′ S ) in a 1:2:1 ratio ().…”
Section: Discussionmentioning
confidence: 99%
“…Strains, culture, and fermentation protocols were developed to increase the yield of cellular astaxanthin (An et al 1989; Johnson and An 1991; Bon et al 1997). Feeding trials with rainbow trout Oncorhynchus mykiss suggested that the degree of pigmentation from Phaffia depended on whether a milled, enzyme‐treated, or extracted astaxanthin from the yeast cells was used as the pigment source (Gentles and Haard 1991; Choubert et al 1995).…”
mentioning
confidence: 99%
“…; Choubert et al . ). In contrast, Atlantic salmon was observed to retain 5.7% and 7.6% of astaxanthin and canthaxanthin, respectively (Buttle et al .…”
Section: Pharmacokinetics Of Astaxanthinmentioning
confidence: 97%
“…Among these are synthetic astaxanthin (Choubert and Heinrich, 1993;Wathne et al, 1998); synthetic canthaxanthin (Torrisen and Naevdal, 1984;Choubert and Heinrich, 1993); astaxanthin from Adonis aestivalis (Kamata et al, 1990); astaxanthin from Phaffia rhodozyma (Binkowski et al, 1993;Choubert et al, 1995); xanthophylls from Tagetes erecta (VernonCarter et al, 1994); carotenoids from red pepper (Yanar et al, 1998); carotenoids from oleoresin paprika (Akhtar et al, 1999); astaxanthin from Haematococcus pluvialis (Sommer et al, 1991); astaxanthin from Rhodobacter capsulatus (Pradal, 1994); and astaxanthin from Pleuroncodes planipes (Coral et al, 1998). When comparative studies were conducted, higher levels of total carotenoid and coloration in trout muscle were found in groups fed synthetic astaxanthin (Roche Carophyll Pink) compared with the natural carotenoids from different sources.…”
Section: Introductionmentioning
confidence: 99%